2009
DOI: 10.1088/0967-3334/30/2/005
|View full text |Cite
|
Sign up to set email alerts
|

Robust ballistocardiogram acquisition for home monitoring

Abstract: The ballistocardiogram (BCG) measures the reaction of the body to cardiac ejection forces, and is an effective, non-invasive means of evaluating cardiovascular function. A simple, robust method is presented for acquiring high-quality, repeatable BCG signals from a modified, commercially available scale. The measured BCG waveforms for all subjects qualitatively matched values in the existing literature and physiologic expectations in terms of timing and IJ amplitude. Additionally, the BCG IJ amplitude was shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
131
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(142 citation statements)
references
References 23 publications
4
131
2
5
Order By: Relevance
“…The prolongation of the RJ interval during Valsalva, which could be explained as a consequence of the decreased venous return during the strain, was already reported in the literature (Inan et al 2008). However, this decrease in venous return was not visible in terms of amplitudes, in contrast to the reduced values of A IJ reported in Inan et al (2009).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The prolongation of the RJ interval during Valsalva, which could be explained as a consequence of the decreased venous return during the strain, was already reported in the literature (Inan et al 2008). However, this decrease in venous return was not visible in terms of amplitudes, in contrast to the reduced values of A IJ reported in Inan et al (2009).…”
Section: Discussioncontrasting
confidence: 84%
“…weight scales, bed, chair). In particular, the RJ interval has been proposed as a surrogate for the pre-ejection period (PEP) (Inan et al 2009, Etemadi et al 2011, Javaid et al 2016, a non-invasive indirect measurement of cardiac contractility (Lewis et al 1977), and, combined with photoplethysmography (PPG), both I and J time occurrences have been shown to be an accurate estimate of arterial stiffening (Wiard 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The signal was obtained by the superposition of several sine functions whose amplitudes and periods were chosen so that the resultant signal shape was similar to a ballistocardiogram. 176,177 In other words, the BCG signal expressed in microstrains with a 4-με amplitude and 1-s period (60 bpm) is presented in the upper graph. The middle graph shows the strain-induced Bragg wavelength shifts of the FBG peak synchronized with the strain changes.…”
Section: Mathcad Simulationsmentioning
confidence: 99%
“…Further, it was observed there that different weighing scales yielded different BCG waveforms for the same subject, albeit this was irrelevant for heart rate monitoring [2]. Unfortunately, these results went mostly unnoticed during later characterizations of weighing scales intended for BCG monitoring [7], which concluded that the measured waveform was not mechanically distorted as the resonant frequency of scales was significantly out of band. This view, in which the mechanic response of the weighing scale is considered not to distort the BCG signal, has been sustained until now [1,8].…”
Section: Introductionmentioning
confidence: 99%